2018
DOI: 10.1111/mcn.12663
|View full text |Cite
|
Sign up to set email alerts
|

Progress and inequalities in infant and young child feeding practices in India between 2006 and 2016

Abstract: Limited evidence exists on socio‐economic status (SES) inequalities in infant and young child feeding (IYCF) in India. We examine trends and changes in inequalities for IYCF practices over 2006–2016 and identify factors that may explain differences in IYCF across SES groups. We use data from the 2015–2016 and 2005–2006 National Family Health Surveys ( n = 112,133 children < 24 months). We constructed SES quintiles (Q) and assessed inequalities using concentration and slope indices. We ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 25 publications
5
33
1
Order By: Relevance
“…While maternal education was more strongly associated with consumption of essential food items and all food groups, household wealth status was significantly associated with consumption of dairy group only. In general our findings are consistent with results from past [21,23,24,31] and recent studies [32] conducted in LMICs and India, which found a positive relationship between measures of individual-level socioeconomic status and specific food item/food group consumption and diversified dietary intake.…”
Section: Discussionsupporting
confidence: 93%
“…While maternal education was more strongly associated with consumption of essential food items and all food groups, household wealth status was significantly associated with consumption of dairy group only. In general our findings are consistent with results from past [21,23,24,31] and recent studies [32] conducted in LMICs and India, which found a positive relationship between measures of individual-level socioeconomic status and specific food item/food group consumption and diversified dietary intake.…”
Section: Discussionsupporting
confidence: 93%
“…We found that higher SES was associated with a 50% decrease in EBF. Likewise, in a recent analysis of India's NFHS 2005and NFHS 2015-2016 datasets higher SES was negatively associated with EBF both directly and indirectly through access to information and services, parity, and urban/rural residence (Nguyen et al, 2018). The systematic review of determinants of EIBF in South Asia highlights differences in the role of sociodemographic factors by region and thus the need for context-specific understanding on breastfeeding determinants (Sharma & Byrne, 2016).…”
Section: Maternal and Household Factorsmentioning
confidence: 99%
“…According to the study [80] that examines trends in the young child feeding practices in India in the period of 2006-2016, breastfeeding practices have shown signi cant improvements: Early initiation of breastfeeding nearly doubled from 23% to 42%, and Exclusive breastfeeding increased from 46% to 55%. However, still, a major cohort of children are missing out and the current rates, at best can be described as modest [80]. Several factors play role in dis-continuation of breastfeeding.…”
Section: Related Work 31 Breastfeeding Practices In India Support Smentioning
confidence: 99%